Training for an International Academic Career: Structuring a Successful PhD Program in Romania - Claudia Urdari; Vlad Andrei Porumb; Ion Anghel (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The worldwide demand of young academics has constantly expanded throughout the last decades. The minimum requirements for entering the global academic labor market have increased and PhD students need to rise up to the expectations of a progressively demanding profession. This paper aims to fill the gap emphasized by several recent studies, which have voiced the need to improve the international competitiveness of Romanian higher education institutions (HEIs). By employing a participative observation study approach, we analyze the characteristics and structure of French business schools' doctoral programs and provide a model of PhD training adapted to the current requirements of the international academic market. Moreover, we highlight the manner in which the curricula adjustments need to be accompanied by additional implementation programs and we underline the need for Romanian universities to make a clear distinction between PhDs and professional doctorates. Along with proposing an integrated model of doctoral training that can raise the international visibility of Romanian PhD programs, we discuss the potential long-term benefits of implementing this model.
Keywords: A23; D83; I21; I23; I25; J21; J23; J24; J31; J45; J61; 650; higher education; internationalization; PhD programs; academic labor market; academic career